Back Cover: Conformational Analysis of an Antibacterial Cyclodepsipeptide Active against Mycobacterium tuberculosis by a Combined ROE and RDC Analysis (Chem. Eur. J. 24/2017). Issue 24 (14th March 2017) - Fredersdorf, Maic; Kurz, Michael; Bauer, Armin; Ebert, Marc‐Olivier; Rigling, Carla; Lannes, Laurie; Thiele, Christina Marie
Abstract : Griselimycin (GM) and methylgriselimycin (MGM) are cyclic depsipeptides that inhibit the sliding clamp of DNA polymerase III of Mycobacterium tuberculosis and are therefore considered as potential anti‐tuberculosis drugs. Methylation increases both stability and activity of MGM compared to GM. The solution structure of MGM was determined using advanced NMR spectroscopy. A highly defined structural model of MGM was obtained, which shows related characteristics to GM bound to DNA polymerase III subunit‐beta. More information can be found in the Full Paper by C. M. Thiele et al. onpage 5729 ff.